PLEISTOCENE-HOLOCENE PALAEOENVIRONMENTAL RECORDS FROM PERMAFROST SEQUENCES AT THE KARA SEA COAST (NW SIBERIA, RUSSIA) - Irina Streletskaya; Evgeny Gusev; Alexander Vasiliev; Gleb Oblogov; Anatoly Molodkov (Geography, Environment, Sustainability, 2013)
The Kara Sea coasts were studied using comprehensive stratigraphic and geocryological methods. The paper presents the new analytical studies of ground ice and Quaternary deposits of Western Taymyr and presents the results of spore and pollen, foraminifera, grain-size, mineralogical, geochemical, oxygen isotopic, and other analyses. Several stratigraphic-geocryological transects from Yenisey and Gydan Bays enable us to refine the stratigraphy and palaeogeographical reconstruction of the environments and freezing of Late Pleistocene-Holocene sediments. Marine sedimentation conditions during the late Kargino time (MIS3) changed to continental conditions in MIS2 and MIS1. Marine sediments were frozen syn- and epigenetically with cryotexture and ground ice formation. Ice wedges formation corresponds to the end of the Pleistocene (MIS2) and during cooler periods of the Holocene.